Improving Performance of Cantilevered Momentum Wheel Assemblies by Soft Suspension Support - Weiyong Zhou; Dongxu Li (Shock and Vibration)
This paper focuses on improving the performance of the rigid support cantilevered momentum wheel assemblies (CMWA) by soft suspension support. A CMWA, supported by two angular contact ball bearings, was modeled as a Jeffcott rotor. The support stiffness, before and after in series with a linear soft suspension support, were simplified as two Duffing's type springs respectively. The result shows that the rigid support CMWA produces large disturbance force at the resonance speed range. The soft suspension CMWA can effectively reduce the force on the bearing (also disturbance forces produced by the CMWA) at high rotational speed, and also reduce the nonlinear characteristic of the stiffness. However, the instability of the soft suspension CMWA will limit the maximum rotational speed of the CMWA. Thus, a "proper" stiffness of the soft suspension system is a trade-off strategy between reduction of the force and extension of the speed range simultaneously.